Roundtable: The Digital Humanities: A Common Ground for Experimentation - Carlos Ceia,; Fátima Vieira,; Federico Boschetti,; Nils Geißler,; Joana Pinela,; Luciano Moreira,; Raquel Correia de Souza,; Joel Ramos Faustino, (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Transcript of Roundtable "The Digital Humanities: A Common Ground for Experimentation"